2021
DOI: 10.1371/journal.pone.0256588
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microRNA expression in B cells derived from Japanese black cattle naturally infected with bovine leukemia virus by deep sequencing

Abstract: Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis (EBL), a malignant B cell lymphoma. However, the mechanisms of BLV-associated lymphomagenesis remain poorly understood. Here, after deep sequencing, we performed comparative analyses of B cell microRNAs (miRNAs) in cattle infected with BLV and those without BLV. In BLV-infected cattle, BLV-derived miRNAs (blv-miRNAs) accounted for 38% of all miRNAs in B cells. Four of these blv-miRNAs (blv-miR-B1-5p, blv-miR-B2-5p, blv-miR-B4-3p, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 127 publications
(103 reference statements)
1
9
0
2
Order By: Relevance
“…However, in our study we did not find any association between blv-miR-b4-3p expression in cattle naturally infected with BLV and HBP-1 mRNA expression levels, compared to the control group (BLV-). In agreement with our observation, Ochiai et al [6] reported that HBP-1 mRNA in B-cells derived from BLV-infected cattle did not differ from those of BLV-negative animals. In a different study, Rosewick and colleagues used an ovine model of BLV infection to describe the expression of BLV-encoded miRNAs in vivo [5].…”
Section: Plos Onesupporting
confidence: 94%
See 2 more Smart Citations
“…However, in our study we did not find any association between blv-miR-b4-3p expression in cattle naturally infected with BLV and HBP-1 mRNA expression levels, compared to the control group (BLV-). In agreement with our observation, Ochiai et al [6] reported that HBP-1 mRNA in B-cells derived from BLV-infected cattle did not differ from those of BLV-negative animals. In a different study, Rosewick and colleagues used an ovine model of BLV infection to describe the expression of BLV-encoded miRNAs in vivo [5].…”
Section: Plos Onesupporting
confidence: 94%
“…In agreement with our observation, Ochiai et al . [ 6 ] reported that HBP-1 mRNA in B-cells derived from BLV-infected cattle did not differ from those of BLV-negative animals. In a different study, Rosewick and colleagues used an ovine model of BLV infection to describe the expression of BLV-encoded miRNAs in vivo [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each DNA sample was tested in duplicate. For the blood and tumor samples of sheep, the BLV tax gene was measured in the DNA samples using real-time PCR, as described previously ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each DNA sample was tested in duplicate. For the blood and tumor samples of sheep, the BLV tax gene was measured in the DNA samples using real-time PCR, as described previously (19).…”
Section: Quantification Of Blv Proviral Load (Pvl)mentioning
confidence: 99%